The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0014479706004224
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm Wheat Trials in Bangladesh: A Study to Reduce Perceived Constraints to Yield in Traditional Wheat Areas and Southern Lands That Remain Fallow During the Dry Season

Abstract: 22H . M . R AW S O N et al. was only 1.5 million t and decreasing. The situation was creating serious concerns for food security and diminishing foreign currency reserves.There are two standard approaches to increasing production: first to look for unused or under-utilized land that might be adapted to wheat cultivation and second to explore ways to increase yield per unit area in current wheat cropping areas. In the second approach yield is increased by reducing perceived environmental and genetic limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Trials spanned eight different production environments chosen with varying levels of soil salinity in coastal southwest Bangladesh. Our objectives were to confirm earlier on-farm study results (e.g., Carberry et al, 2011;Rawson et al, 2007), indicating that wheat can be used to achieve system intensification objectives in this stress-prone region, and to help establish efficient recommendations for N management as a function of sowing date and genotype in saline-affected deltaic environments that are common in Bangladesh, but which may also have applicability in similar environments such as in West Bengal, in India.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Trials spanned eight different production environments chosen with varying levels of soil salinity in coastal southwest Bangladesh. Our objectives were to confirm earlier on-farm study results (e.g., Carberry et al, 2011;Rawson et al, 2007), indicating that wheat can be used to achieve system intensification objectives in this stress-prone region, and to help establish efficient recommendations for N management as a function of sowing date and genotype in saline-affected deltaic environments that are common in Bangladesh, but which may also have applicability in similar environments such as in West Bengal, in India.…”
Section: Introductionsupporting
confidence: 63%
“…Research in less-favorable environments -for example those located in coastal and deltaic areas with environmental stresses -is less frequent, as is work conducted in farmers' fields, where bio-physical and socio-economic diversity typically necessitates site-specific management strategies (e.g., Erenstein et al, 2008;Rawson et al, 2007). In southern Bangladesh, we assessed management options for farmers cultivating wheat for the first time on formerly fallow land.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated maize Yp in this study is lower than those reported by Timsina et al, 2010 , Timsina et al, 2011 , the simulated Yp of rice is similar. Likewise, the simulated Yp for wheat across the country is slightly lower than that recorded from well-managed trials from large numbers of fields ( Rawson et al, 2011 ) as well as also lower than those reported by Timsina and Humphreys (2006) . The discrepancies in simulated and observed yields for rice are expected as the Yp for boro rice in this study was averaged for eight locations of Bangladesh using observed weather data while the Yp from Timsina et al, 2010 , Timsina et al, 2011 was based on only three locations and simulated using the NASA weather data.…”
Section: Discussionmentioning
confidence: 61%
“…The land growth is still occurring (Rawson et al, 2006). During the Kharif season, they are cropped with T. Aman or T. Aus rice, irrigated by the fresh waters of the monsoon, but in the Rabi season, the salt rises as the land dries and crusts are formed on the surface, making it unsuitable for productive cropping.…”
Section: Introductionmentioning
confidence: 99%